“It's My Country I'm Playing for”—A Biographical Study on National Identity Development of Youth Elite Football Players With Migrant Background - Seiberth, Klaus; Thiel, Ansgar; John, Jannika M. (Frontiers in Sports and Active Living, 2022)
Sport represents a prominent topic for public and scientific debates on national identity. Looking at Germany, public discourses on national belonging have primarily focused on national elite football and on German-born international football players with Turkish background. Representing the biggest ethnic community in Germany and being highly represented in German youth elite football, athletes with Turkish background are prime examples for the complexity and ambiguity of identity formations in modern immigration countries in general and in youth elite football in particular. Current research has particularly focused on national identity formations of (youth) elite players with migrant background. However, there is a lack of studies that address the process of national identity development in youth elite sport. For that reason, the study aimed to explore stories of national identity development from the perspective of youth football players with Turkish background in German youth elite football. By conducting 10 expert interviews and biographical mappings, we identified specific types, strands, and trajectories of national identity development. Overall, we identified three types of narratives on national identity development: “going with the nomination(s),” “reconsidering national belonging,” and “adding up chances”. Our findings illustrate that national identity development in youth elite sport is particularly shaped by youth elite sport and the national team question. Hence, the stories indicate that international careers not necessarily foster national identification with a nation but can also reduce feelings of national belonging sustainably.